2011
DOI: 10.1074/jbc.m111.274910
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 2 Stimulation of Osteoblast Differentiation and Bone Formation Is Mediated by Modulation of the Wnt Signaling Pathway

Abstract: Fibroblast growth factor 2 (FGF2) positively modulates osteoblast differentiation and bone formation. However, the mechanism(s) is not fully understood. Because the Wnt canonical pathway is important for bone homeostasis, this study focuses on modulation of Wnt/␤-catenin signaling using Fgf2 Both embryonic and postnatal skeletogenesis involve mesenchymal precursor cells progressively differentiating into boneforming cells, osteoblasts (1). Osteoblast differentiation is controlled by extracellular signals, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 65 publications
3
83
0
Order By: Relevance
“…Thus, the profound effect on bone seen in mice with a conditional deletion of β-catenin exon 3, which prevents this basal ubiquination of β-catenin, would be expected to reflect a decoupling from both the WNT and FGF2/ MEKK2 pathways (1,24). Notably, these findings provide a mechanistic basis for prior observations that β-catenin protein levels and activity are reduced in the absence of FGF2 (25). The phenotype of Mekk2 −/− mice also is consistent with the reduced bone mass and decreased BFR seen in adult Fgf2 −/− mice, indicating that a FGF2/MEKK2 pathway contributes to the maintenance of adult bone mass (26).…”
Section: Discussionmentioning
confidence: 52%
“…Thus, the profound effect on bone seen in mice with a conditional deletion of β-catenin exon 3, which prevents this basal ubiquination of β-catenin, would be expected to reflect a decoupling from both the WNT and FGF2/ MEKK2 pathways (1,24). Notably, these findings provide a mechanistic basis for prior observations that β-catenin protein levels and activity are reduced in the absence of FGF2 (25). The phenotype of Mekk2 −/− mice also is consistent with the reduced bone mass and decreased BFR seen in adult Fgf2 −/− mice, indicating that a FGF2/MEKK2 pathway contributes to the maintenance of adult bone mass (26).…”
Section: Discussionmentioning
confidence: 52%
“…In osteoprogenitor cells, FGF2 was found to antagonize WNT/β-catenin signaling Ambrosetti et al 2008). In vivo, however, Wnt genes are decreased significantly in osteoblasts from Fgf2 −/− mice, which display reduced osteoblast differentiation (Fei et al 2011). Consistent with this, exogenous FGF2 can promote β-catenin nuclear accumulation and rescue osteoblast differentiation in Fgf2 −/− mice, indicating that endogenous FGF2 stimulates cell differentiation in more mature osteoblasts in part by activating WNT/β-catenin signaling (Fei et al 2011).…”
Section: Intramembranous Mesenchymal Condensationsmentioning
confidence: 99%
“…FGF/FGFR signal and canonical Wnt/β-catenin pathway had complicated interaction. The loss of efficiency of Wnt inhibitor Axin2 could lead to craniosynostosis of mice [95,96]. Experiments of Liu et al [95] showed that lack of Axin2 could promote β-catenin signal and ultimately cause ossification of periosteum.…”
Section: Fgf/fgfr Signal Regulating Bone Metabolismmentioning
confidence: 99%
“…Wnt-dependent BMP signals could guide intracellular β-catenin distribution, featuring an important positive feedback regulation effect upon β-catenin [96]. FGF signal and BMP signal, apart from the Wnt/ β-catenin mediated indirect relations, also shared certain direct relations.…”
Section: Fgf/fgfr Signal Regulating Bone Metabolismmentioning
confidence: 99%
See 1 more Smart Citation